The New England Litogrphic Company; Amoskeag Manufacturing Company. Steam Fire Engines - Sampson, Davenport, & Co. (Tufts Archival Research Center, 2005)
Page image of The New England Litogrphic Company; Amoskeag Manufacturing Company. Steam Fire Engines from the 1870 Boston City Directory